The Impact of Financial Technology on Commercial Banks: A Case Study of China - Zhou, Tian Xiang (Secholian Publication (Kuala Lumpur, Malaysia), 2023)
The aim of the research was to investigate the impact of financial technology on the financial performance of commercial banks. in China. Based on previous literature review and empirical evidence this study collects the annual financial data on local banks in China. A total of 23 commercial banks were used as sample of the study. The annual data ranges from 2011 to 2020. The data was analysed using GMM dynamic panel data model. Based on the analysis, the findings showed that financial technology has an overall positive impact on the return on asset of commercial banks.